An Elephant & Piggie Biggie! - Willems, Mo (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2017)
For the first time ever, best friends Elephant and Piggie have five Biggie adventures in one book!
Today I will fly! -- Watch me throw the ball! -- Can I play too? -- Let's go for a drive! -- I really like slop!
Illustrations on lining-papers.
Keywords: Swine -- Juvenile fiction; Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Play -- Juvenile fiction; Swine -- Fiction; Elephants -- Fiction; Friendship -- Fiction; Cooperativeness -- Fiction; Play -- Fiction; JUVENILE FICTION -- Animals -- Elephants; JUVENILE FICTION -- Animals -- Pigs; JUVENILE FICTION -- Humorous Stories; Cooperativeness; Elephants; Friendship; Play; Swine; Pigs -- Fiction; Friendship -- Fiction; Elephants -- Fiction; Picture books for children; Picture books for children; Readers (Publications); Picture books; Fiction; Juvenile works; Short stories; Readers (Publications); Humorous fiction